HIE Enterprise Architecture: Frameworks and Governance for Public Healthcare - Yadav, Kumar Amodh (International Journal of Computing and Engineering, 2025)
This article presents a comprehensive analysis of Enterprise Architecture deployment for State-Wide Health Information Exchanges (HIEs) in public healthcare systems. The article examines the technical frameworks, governance models, consent management approaches, and clinical decision support capabilities that underpin successful HIE implementations. Through critical evaluation of architectural patterns, including Service-Oriented Architecture, FHIR-based APIs, and cloud-native platforms, the article identifies effective integration strategies for diverse healthcare environments. The article explores governance structures ranging from centralized to federated models, highlighting the sustainability advantages of hybrid approaches and public-private partnerships. Patient privacy protection is addressed through analysis of consent management frameworks, from opt-out models maximizing data availability to granular opt-in systems providing fine-grained control. The article concludes with an examination of real-time alerting systems and clinical decision support capabilities, demonstrating their impact on care coordination, readmission reduction, and clinical outcomes. Throughout, the article emphasizes the sociotechnical nature of HIE implementation, where success depends on balancing technical architecture with organizational governance and stakeholder alignment.